2021
DOI: 10.1111/acel.13484
|View full text |Cite
|
Sign up to set email alerts
|

CDK2 phosphorylation of Werner protein (WRN) contributes to WRN’s DNA double‐strand break repair pathway choice

Abstract: Werner syndrome (WS) is a rare autosomal recessive genetic disorder caused by mutation in the WRN gene (Bohr, 2005). This premature aging disorder is characterized by scheduled hierarchical deterioration of connective tissue and of the endocrine-metabolic system, as also seen in other diseases of accelerated aging (Oshima et al., 2017).WS patients suffer from cancer, diabetes, cardiovascular disease, and die at a median age of 54 (Huang et al., 2006). WS patients also have much higher incidence of sarcomas tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Extensive biochemical studies of the pathologies of WS have been focused mainly on DNA damage 1 , 2 , genomic instability 2 , and mitochondrial homeostasis 9 . Patients with WS or those with cells missing WRN are highly susceptible to DNA-damaging agents, highlighting the critical involvement of WRN in DNA repair 10 . However, the mechanism behind the short stature in WS patients remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive biochemical studies of the pathologies of WS have been focused mainly on DNA damage 1 , 2 , genomic instability 2 , and mitochondrial homeostasis 9 . Patients with WS or those with cells missing WRN are highly susceptible to DNA-damaging agents, highlighting the critical involvement of WRN in DNA repair 10 . However, the mechanism behind the short stature in WS patients remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin-dependent kinase 2 (CDK2) is a critical cell cycle regulator of G1/S [1][2][3][4][5]. CDK2 is also involved during DDR, HR, signal transduction, apoptosis, and DNA and RNA metabolism in cells [6][7][8][9][10]13]. Here, we comprehensively evaluated CDK2 in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Besides playing a critical role in cell cycle progression, CDK2 is also involved in the DNA damage signalling response (DDR) in cells [6][7][8][9][10]. CDK2 has been shown to be involved during the homologous recombination (HR) pathway via activation of MRN-CtIP-BRCA1, which is essential for the repair of DNA double-strand breaks [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the classical function of the pathogenic genes has been well characterized, their novel roles in regulating genome stability are still to be investigated. A recent paper has shown that Werner protein (WRN) participates in the regulation of HR/NHEJ pathway choice in a CDK2-dependent manner (Lee et al, 2021). Moreover, in HGPS cells, the NER factor XPA mysteriously colocalizes with γ-H2AX, the marker of DSB (Liu et al, 2008), and the BER capacity also decreases, attributing to the reduced expression or activity of several BER factors in HGPS cells (Maynard et al, 2019).…”
Section: Age-associated Alterations In Genome Stability: Mechanisms A...mentioning
confidence: 99%